Efektivitas Pelatihan Kompos dan Pemberian Kit Komposter pada Warga Perumahan Batan Indah Tangerang Selatan - Akhyar, Muhammad; Untoro, Vinaya (Fakultas Psikologi Universitas Pancasila, 2022)
This study aims to determine the effectiveness of training in home composting for residents in Batan Indah Tangerang housing estate. A total of 20 residents of the Batan Indah participated in the home composting training by BRIN (National Research and Innovation Agency). Only 12 residents participated to fill the training effectiveness questionnaire. The results show that although there are still obstacles to composting, home composting effectively increases other pro-environmental behaviors (spill-over behavior). After the training, there is an increase in the intensity of sorting waste behavior and a reduction in wastefulness. Home composting is still seen as an effective strategy to create a sustainable environment at the household level.